Implementasi Infrastruktur Jaringan Untuk Mendukung Program Sertifikasi SMA Islam Kepanjen Kabupaten Malang - Yuri Ariyanto; Yan Watequlis Syaifudin; Budi Harijanto; Dwi Puspitasari; Chandrasena Setiadi; Mungki Astiningrum (Jurnal Pengabdian kepada Masyarakat, 2024)
The Community Service Program intends to support the Empowering School Certification Program by establishing computer network infrastructure at the Islamic High School in Malang's Kepanjen region. According to analysis studies, the current network falls short of the online access criteria for certification tests. This intervention employed two essential approaches. The first option entails installing standard-based computer networks in the school laboratory facilities. The second option gives information technology (IT) educators extensive network management support. The Community Service Program Team of the State Polytechnic of Malang runs the initiative, which focuses on creating a reliable network topology and increasing the skills of the school's IT staff. This intervention is expected to increase overall educational quality and develop network infrastructure that will allow certification programs to be implemented. The accompanying seeks to provide expertise to Kepanjen's Islamic High School Team so that they can manage the network more independently. This community service project is designed to optimize the digital learning ecosystem, improve education and evaluation processes, and prepare students for the complexities of the digital age. This will be accomplished through collaboration between the Community Service Program team and the Islamic High School of Kepanjen District Malang.